Evaluating the Role of Fosfomycin Activity Against Extended-Spectrum-Β-Lactamase- Producing Escherichia Coli and Klebsiella Pneumonia Isolated in Clinical Isolates - Sinha, Sarita; D Kandpal, Vikas; Pal, Ashish; Afaq, Nashra; Rai, Arpita; Kumar Patwa, Mukesh; Kumar, Deepak (Journal of Neonatal Surgery, 2025)
Background: The management of infections in hospital settings has become considerably more difficult due to the emergence of Escherichia coli and Klebsiella pneumoniae that produce extended-spectrum beta-lactamases (ESBLs). Due to a lack of available treatments, interest in the efficacy of substitute antibiotics such as fosfomycin has grown. In a tertiary care hospital in India, this study sought to determine the in vitro susceptibility of K. pneumoniae and E. coli that produce ESBL to fosfomycin. Aim and Objective: Evaluating the role of fosfomycin activity on ESBL producing Klebsiella Pneumoniae and E. Coli isolated in clinical isolates. Methods: A total of 210 ESBL-producing isolates (E. coli n=126, K. pneumoniae n=84) were collected from various clinical specimens, including urine, pus, respiratory secretions, and wound swabs. ESBL production was confirmed using the combined disc method. Fosfomycin susceptibility was assessed using the disc diffusion method. Results were interpreted according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: In the present study a total of 210 ESBL-producing isolates, comprising Escherichia coli and Klebsiella pneumoniae, were included. In the current study 210 ESBL-producing isolates were found out of which 62.8% were from male patients and 37.1% from female patients.Among E. coli isolates, 65% were from males and 34.9% from females and in K.pneumoniae isolates, 59.5% were from males and 40.4% from females. This indicates a higher prevalence of ESBL-producing infections among male patients compared to females in this study. The majority of ESBL-producing isolates were found in patients aged 51–70 years (42.8%). Among E. coli isolates, 44.4% were from patients in the 51–70 age group. Fosfomycin demonstrated high in vitro activity against ESBL-producing Escherichia coli and Klebsiella pneumoniae, with 90.4% of E. coli and 78.5% of Klebsiella pneumoniae being susceptible by disc diffusion. Conclusion: Particularly for urinary tract infections, fosfomycin showed strong in vitro action against K. pneumoniae and E. coli that produce ESBL. In situations where antibiotic resistance limits existing treatment options, this study supports the possible use of fosfomycin as an effective alternative. These findings indicate that fosfomycin is a viable treatment option for infections caused by ESBL-producing E. coli and K. pneumoniae in tertiary care hospitals.